Trends and Patterns of Mathematical Literacy Research In Indonesia: A Systematic Literature Review - Shafira, Syifa; Yulianti, Kartika; Martadiputra, Bambang Avip Priatna; Dahlan, Jarnawi Afgani (JRPM (Jurnal Review Pembelajaran Matematika), 2026)
This study aimed to examine trends and patterns in mathematical literacy research in Indonesia, as an essential component of mathematics education. Using a systematic literature review, this study analyzed 18 Scopus-indexed articles published between 2021 and 2025. This study examined the distribution of publications across journal quartiles, years, geographic research sites, research methods, mathematical topics, and educational levels. The results showed an upward trend in publications in recent years, with most studies appearing in mid-tier journals. Among the reviewed studies, qualitative methods were the most frequently employed research approach. The investigated topics were mainly concentrated on shape and space, and most studies focused on the junior high school level, while other levels received less attention. In addition, research sites were unevenly distributed, with concentrations in certain provinces. These findings indicate that mathematical literacy research in Indonesia has developed steadily but remains concentrated in specific contexts, offering opportunities for broader coverage in future studies.